Selective aptamer conjugation to silver-coated magnetite nanoparticles for magnetic solid-phase extraction of trace amounts of Pb2+ ions. Issue 9 (27th January 2021) - Rahnama, Sara; Shariati, Shahab; Divsar, Faten
Abstract : Herein, a novel aptamer-functionalized magnetic adsorbent was developed and combined with magnetic solid-phase extraction (MSPE) for the specific enrichment of Pb 2+ ions prior to flame atomic absorption spectrometric detection. Abstract : Herein, a novel aptamer-functionalized magnetic adsorbent was developed and combined with magnetic solid-phase extraction (MSPE) for the specific enrichment of Pb 2+ ions prior to flame atomic absorption spectrometric detection. First, silver-coated magnetite core–shell nanoparticles (Fe3 O4 @Ag MNPs) were synthesized by the chemical reduction of silver ions on the surface of magnetite nanoparticles. After that, the selective DNA aptamer against Pb 2+ was conjugated on the surface of the synthesized nanoparticles to form aptamer-modified magnetic nanoparticles (Fe3 O4 @Ag-APT). The characterization of the prepared adsorbent was performed through SEM imaging, XRD, FT-IR, EDX, and DRS instruments. The influence of the various experimental parameters on the adsorption and desorption steps in MSPE was investigated via Taguchi experimental design to optimize different parameters. Under the optimized conditions, the Pb 2+ calibration graph was linear in the range of 33–1000 μg L −1 . The relative standard deviation (RSD%) of the method for six replicates containing 100 μg L −1 of Pb 2+ ions was 0.34%. Furthermore, the limit of detection (LOD) and the limit of quantification (LOQ) were 10 μg L −1 and 33.3 μg L −1, respectively. Finally, the applicability of the proposed method was successfully confirmed by preconcentration and determination of trace amounts of Pb 2+ ions in tap and seawater samples. We showed a proof of concept for Fe3 O4 @Ag-APT as an efficient bio-adsorbent, offering a promising strategy for the specific binding/removal of toxic heavy metal ions.